METHODS OF ASSESSING THE HYGIENIC CONDITION OF THE ORAL CAVITY IN CHRONIC GENERALIZED PERIODONTITIS CAUSED BY EXTREME CLIMATE - Mirraximova S.Sh.; Jaxonaliyev B.U. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Periodontal diseases of inflammatory origin are considered to be the main dental diseases, as for many decades they have been the most common among other diseases of the maxillofacial region. The Toothpaste Effectiveness Index was used to objectively evaluate toothpastes. This index allows for a more specific evaluation, selection of the most effective products among similar groups, and qualitative assessment, expressed as points for each criterion.